AppAware: a policy visualization model for mobile applications. (23rd January 2020) - Paspatis, Ioannis; Tsohou, Aggeliki; Kokolakis, Spyros
Abstract : Purpose: Privacy policies emerge as the main mechanism to inform users on the way their information is managed by online service providers, and still remain the dominant approach for this purpose. The literature notes that users find difficulties in understanding privacy policies because they are usually written in technical or legal language even, although most users are unfamiliar with them. These difficulties have led most users to skip reading privacy policies and blindly accept them. This study aims to address this challenge this paper presents AppAware, a multiplatform tool that intends to improve the visualization of privacy policies for mobile applications. Design/methodology/approach: AppAware formulates a visualized report with the permission set of an application, which is easily understandable by a common user. AppAware aims to bridge the difficulty to read privacy policies and android's obscure permission set with a new privacy policy visualization model. Thus, we propose AppAware parser, a mobile add-on that acts complementary with AppAware and helps mobile device users to monitor the applications they installed to their smart device. Findings: To validate AppAware, the authors conducted a survey through questionnaire aiming to evaluate AppAware in terms of installability, usability and viability-purpose. The results demonstrate that AppAware is assessed above average by the users in all categories. Originality/value: In the best of the authors' knowledge, there is no such approach as AppAware as an application nor AppAware parser as add-on.